Commitment of medical graduates educated with and without community-based medical education towards community health care: a study from Malaysia - Hassan, Shahid (KKMED Publication, 2013)
Context: Community-based medical education (CBME) has become widely accepted as an important innovation in undergraduate medical education. In curriculum featuring CBE, students are acquainted with the community early in their studies however; the impact of this training can be judged best to see them practice the required aspects of CBME. Malaysia is a multiracial country with a very strong community dependant life style. Main national health problems have called for a change in health profession education from traditional hospital based health care to community-based delivery system. There are three major university medical schools that practice either community oriented or community based medical education in undergraduate medical curriculum. Universiti Sains Malaysia (USM) has a community based medical education (CBME) curriculum as compared to a community oriented education curriculum (COE) adopted by Universiti Malaya (UM) and a more traditional curriculum practiced by Universiti Kebangsaan Malaysia (UKM). Objective: To determine whether medical graduates from USM with a community-based medical education in its curriculum for more than 25 years are inspired to have stronger commitment towards community health as shown during their on-job practice of medicine compared to other graduates from UM and UKM, who have adopted community-oriented medical education. Methods: A questionnaire-based pilot study with 12 items (variables) was designed to obtain supervisor’s opinion on commitment of interns towards the health of community they serve. The questionnaire was administered to a randomized group of 85 specialists supervising the internship training program in five major disciplines including internal medicine, surgery, orthopedic, gynecology and obstetrics and pediatric medicine. The data received from 62 respondents from four major disciplines was analyzed utilizing SPSS version 12.0.1. Result: The responses received from 62 supervisors on 9 out of 12 variables were directly related to community commitments of interns. It was shown that the USM graduates who were taught through a CBME curriculum have performed better than the graduates from UM and UKM who followed a COE curriculum. p-value (< 0.001) was highly significant and consistent with higher mean score in those variables. Conclusion: The graduates taught through a CBME curriculum (USM) performed better in community commitments towards patients care compared to graduates from COE curriculum (UM) and a traditional curriculum (UKM).